Peningkatan pengetahuan masyarakat tentang stigma pada penderita kusta - Umi Romayati Keswara; Andoko Andoko; Rahma Elliya (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: The disease of leprosy is one of the most prevalent infectious diseases in Lampung Province, both medically and socially. Data from the World Health Organization (WHO) recorded a prevalence of 0.2 per 10,000 population, with 208,619 new patients occurring throughout 2018. In Indonesia, the number of new cases of leprosy is 14,397 with a detection rate of 5.43 per 100,000 population. In addition, there are a total number of 19,033 cases of leprosy, with a prevalence rate of 0.72 per 10,000 population. One of the problems that hinder efforts to control leprosy is the stigma of it, and the lack of public knowledge about stigma in people with leprosy.Purpose: Increasing public knowledge about the negative stigma of patients with leprosy.Method: Quantitative research type, with a Quasi-Experimental group pre-test post-test design. The population of the people of Sidodadi Asri Village, the Working Area of the Banjar Agung Inpatient Health Center, with a sample of 30 patriarchs. Dependent T-Test data analysis.Results: The average knowledge of the community about stigma before health education was 29.5 with a standard deviation of 2.82 and a minimum value of 23, after health education of 32 with a standard deviation of 2.15 and a minimum value of 25, p-value 0.000 < = 0.Conclusion: There is an effect of health education on increasing public knowledge about stigma in leprosy patients. Suggestions, health education can be used to increase public awareness of negative stigma of patients with leprosy.Keywords: Knowledge; Public Stigma; Leprosy; Health education.Pendahuluan : Penyakit kusta merupakan salah satu penyakit menular yang menjadi masalah kesehatan di Propinsi Lampung, baik aspek medis maupun social. Data World Health Organization (WHO), mencatat prevalensi 0,2 per 10.000 penduduk, dengan jumlah pasien baru 208.619 kasus terjadi sepanjang 2018. Di Indonesia jumlah kasus baru kusta 14.397 dengan case detection rate 5,43 per 100.000 penduduk dengan jumlah total kasus kusta 19.033 dengan angka prevalensi 0,72 per 10,000 penduduk. Salah satu masalah yang menghambat upaya penanggulangan kusta adalah adanya stigma terhadap penyakit kusta, kurangnya pengetahuan masyarakat tentang stigma pada penderita penyakit kusta.Tujuan : Meningkatkan pengetahuan masyarakat tentang stigma pada penderita kusta.Metode : Jenis penelitian Kuantitatif, dengan Quasi Experimental One group pre-test post-test design. Populasi masyarakat Desa Sidodadi Asri Wilayah Kerja Puskesmas Rawat Inap Banjar Agung dengan, sampel 30 Kepala Keluarga. Analisa data Dependent T Test.Hasil : Rata-rata pengetahuan masyarakat tentang stigma sebelum pendidikan kesehatan sebesar 29,5 dengan standar deviasi 2,82 nilai minimal 23, setelah pendidikan kesehatan sebesar 32 dengan standar deviasi 2,15 nilai minimal 25, p- value 0,000 < α = 0,05.Simpulan: Ada pengaruh pendidikan kesehatan terhadap peningkatan pengetahuan masyarakat tentang stigma pada penderita kusta. Saran, pendidikan kesehatan dapat digunakan sebagai salah satu cara untuk meningkatkan pengetahuan masyarakat tentang stigma pada penderita kusta.